Texture and precipitation behavior of friction stir welded Inconel 825 alloy. (December 2020) - Das, Hrishikesh; Mondal, Mounarik; Hong, Sung-Tae; Lee, Ji-Woo; Cho, Hoon-Hwe
Highlights: The butt FSWed region of Inconel 825 consisted of two different regimes. With DRX in the SZ, the maximum LAGBs and minimum HAGBs occurred in the TMAZ. The frequency of CSL greatly diminished from the BM to the SZ and TMAZ. Nano-precipitations were formed in the grains and at the grain boundaries. Precipitations and refined grains enhanced the mechanical properties of the joint. Abstract: The microstructure, texture pattern, and precipitation behavior of friction stir butt welded Inconel 825 alloy are highlighted here. The microstructure of bright regions and black-banded regions in the stir zone (SZ) is characterized by SEM, EBSD and TEM with EDS. EBSD analysis justifies that the SZ exhibits a dynamic recrystallized structure. Grain boundary mapping corroborates the insignificant difference in the low- and high-angle grain boundaries fraction between the SZ, the thermo-mechanically affected zone, and the base metal. TEM analysis confirms the formation of nano twins and dispersion of nano-size precipitations in the grains, and at the grain boundaries as well. Grain refinement and nano-size precipitation formation in the SZ significantly enhanced both microhardness and tensile strength.